City Authorities of Ekaterinburg and the Development of Education during the First World War: Higher Primary Schools - Liudmila Aleksandrovna Dashkevich (Известия Уральского федерального университета. Серия 2: Гуманитарные науки)
This article examines the participation of the Ekaterinburg City Duma in the development of urban education during the First World War. It is established that, despite the difficult conditions of the war and the change of government, the opening of higher primary schools and professional courses under them was one of the priorities of the city authorities. Most higher primary school students came from bourgeois families and peasants. Higher primary schools not only provided them with completed primary education but also gave them an opportunity to continue their education in secondary schools provided they passed an exam in foreign languages. The City Duma approved the introduction of German, French, and English into the curriculum of higher primary schools. The article presents a plan for the creation of a special network of higher primary schools in Ekaterinburg city and its uyezd, developed at a uyezd meeting on the promotion of advanced primary education. The meeting took place in Ekaterinburg on November 12, 1915. It is concluded that the high level of self-organisation of society and the cultural experience of the city elite allowed the Ekaterinburg authorities to attract public funds to organise professional courses in the city. They were mostly made up of graduates from higher primary schools. The city authorities achieved the creation of chemical and technical courses at the 1st Higher Primary School (1916) and drawing and construction courses at the 2nd Higher Primary School (1915). The courses were free for students. Their work was financed by funds from the treasury, city, and zemstvo. The creation of professional courses was a definite response to the challenges that the city and the country faced during the First World War. Chemical-technical courses laid the foundation for the Ural school of chemical engineers. Drawing and construction courses gave rise to special construction and architectural education.